Efektivitas Modul Ajar Berbasis Problem Based Learning Terintegrasi Geogebra untuk Meningkatkan Kemampuan Berpikir Kritis Mahasiswa - Padang, Nely Salu; Nirfayanti; Narew, Ignasius (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2025)
Critical thinking skills are essential for students to face the demands of the digital era and global competition. However, learning in higher education often remains conventional and does not optimally support the development of higher-order thinking. This study aims to examine the effectiveness of a Problem-Based Learning (PBL) teaching module integrated with GeoGebra in improving students’ critical thinking skills and to explore their learning perceptions. The research employed a quantitative quasi-experimental method with a nonequivalent control group design. A total of 20 students participated, divided into an experimental group using the PBL–GeoGebra module and a control group using a conventional economic mathematics module. Data were collected through pre-test and post-test critical thinking assessments as well as perception questionnaires. Descriptive and inferential analyses were performed using independent t-tests with SPSS for Windows. The results indicate a significant difference between groups, with the experimental group showing higher improvement in critical thinking skills. Students also conveyed positive perceptions of the module, noting increased motivation, active engagement, and improved conceptual understanding through interactive visualization. These findings demonstrate that the PBL–GeoGebra module is effective in enhancing critical thinking skills and provides a more meaningful and applicable learning experience suitable for use as an innovative alternative in higher education.